Article history: Received March 29, 2024 Revised August 20, 2024 Accepted Nov 18, 2024 Keywords: Learning Media, Puzzles, Plant Reproduction Implementasi Pengembangan Media Puzzle Kreatif Pada Materi Perkembangbiakan Tumbuhan Pelajaran IPAS Di Kelas 4 - Anggraeni, Dita Wahyu; Nuruddin, Muhammad; Asmarani, Ratih (IJPSE Indonesian Journal of Primary Science Education, 2024)
The aim of this research is to develop puzzle media for IPAS plant reproduction. This research uses the ADDIE model which has 5 stages, namely: Analysis, Design, Development, Implementation, Evaluation. The aim of this research is to determine the development of puzzle media and the feasibility of the puzzle media. This research uses a questionnaire to test the suitability of the media through media expert validation and material expert validation. The media expert validation results show that the results are categorized as "very valid" with a maximum score of 48 and a gain score of 42 and an average percentage of 87%. Meanwhile, material expert validation shows that the results are categorized as "very valid" with a maximum score of 36 and a score of 33 and an average percentage of 92%. The results of the student response questionnaire were categorized as "very good" with a maximum average score of 60 and an average score of 57 with a percentage of 96%. Thus it can be concluded that puzzle media is suitable for use.